Analisis Pengaruh Program Indonesia Pintar, Program Keluarga Harapan Terhadap Indeks Pembangunan Manusia di Provinsi Gorontalo 2019-2024 - Abdul Hamid, Marsela; Endang Saleh, Sri; Indriyani S. Dai, Sri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of the Indonesia Smart Program (PIP) and the Family Hope Program (PKH) on the Human Development Index (HDI) in Gorontalo Province from 2019 to 2024. Using a quantitative approach and panel data analysis, this research examines the contribution of both programs to the key dimensions of HDI—health, education, and economic welfare. The findings reveal that PKH has a positive and statistically significant effect on HDI, as reflected by a probability value of 0.000, which indicates strong significance. Meanwhile, PIP also shows a positive direction of influence, but it is not statistically significant. Overall, both programs contribute 97% to the variation in HDI in Gorontalo Province. These results highlight the essential role of government intervention in improving human development, although the effectiveness of PIP implementation still requires improvement.